Measurement of ionization in direct frequency comb spectroscopy - Lomsadze, Bachana; Fehrenbach, Charles W.; DePaola, Brett D. (My University, 2013)
Direct frequency comb spectroscopy is currently one of the most precise techniques for studying the internal structure of atomic and molecular systems. In this technique, a train of ultrafast laser pulses excites states in the target system which then relax, emitting fluorescence. The measured fluorescence is then plotted as a function of the comb parameters. But according to recent theory, the ultrashort pulses from the comb laser can also significantly ionize the target. Here, we test this theory by measuring the ion signal from direct frequency comb spectroscopy. Furthermore, instead of actively controlling the frequency comb parameters, we allow them to drift passively, measuring them and the ion signal simultaneously. The experiments were found to be in satisfactory agreement with theory, and the passive comb approach was found to be functional, though not as convenient as the conventional actively locked comb.
Keywords: Direct frequency comb spectroscopy; Atomic and molecular systems